The Biophysical Modeling of the Transport Phenomena in the Living Systems - Janos Vincze; Gabriella Vincze-Tiszay (Technium: Romanian Journal of Applied Sciences and Technology, 2020)
This article describes the principles of biological transport. The transport phenomena mean the variation in time and space of generalized forces when they generate flows for which conservation laws apply. After we describes: mass-, impulse-, energy- and electric-charge-transport and their mathematical characteristic equations. It emphasizes the physical aspects of transport and examines the assumptions and concepts underlying the equations most widely used to characterize transport. In the living organisms, flows are not generated only by the conjugated generalized forces, but also by the simultaneous action of other forces, so appears the cross-effects. The biophysical modeling offer a „language” of quantitative and qualitative processsing of experimental data, being compatible and adequate to the laws of biology.